Pengaruh Likuiditas (FDR) dan Risiko Pembiayaan (NPV) terhadap Kinerja Keuangan (ROA) PT Bank Muamalat Indonesia Tbk (2021-2023) - Nabila Khoirunnisa; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of liquidity, measured by the Financing to Deposit Ratio (FDR), and financing risk, measured by Non-Performing Financing (NPF), on the financial performance of PT Bank Muamalat Indonesia Tbk during the 2021–2023 period. A descriptive quantitative approach was employed, using secondary data from quarterly financial reports, analyzed through multiple linear regression. The results indicate that neither FDR nor NPF had a significant influence on Return on Assets (ROA), whether partially or simultaneously. These findings suggest that both variables do not sufficiently explain fluctuations in financial performance, which may instead be driven by other factors such as operational efficiency and capital structure. Therefore, a more comprehensive financial management strategy is needed to enhance profitability in Islamic banking institutions